PENGARUH GOOD CORPORATE GOVERNANCE DAN FIRM SIZE TERHADAP KINERJA KEUANGAN (ROA) - Mohammad Iskak Elly; Elok Dwi Vidiyastutik; Nurul Izzah (Ecobuss, 2023)
This research aims to determine the influence of good corrporate governance and firm size on financiial performance (ROA). 84 property and real estate companiies listed on the Indonesia Stock Exchange in 2019-2021 are the population in this study. The sample in this rese.arch was 18 companies using a purposiive sampliing technique method and the total sample for 3 years was 54 property and real estate companies that would be analiyzed. The results of this research show that GCG consiists of 5 indicatoirs, namely managerial ownershp, independent board of commiissoners, board of directors partiially influence fiinancal performance, whle institutiionail ownership and the audit commitee partially have no influence on financiial performance. Firm size partially influences financial performance. Simultanneously, the variiables good corporate governnance and firm size have an influence on financial performance. Firm size indicators predominantly have an influence on financial performance.